Geometrical, electronic structure, nonlinear optical and spectroscopic investigations of 4-(phenylthio)phthalonitrile dye sensitizer for solar cells using quantum chemical calculations - Anbarasan, Ponnusamy Munusamy; Kumar, Palanivel Senthil; Vasudevan, Kolandan; Govindan, Raji; Prakasam, Annamalai; Geetha, Munusamy (European Journal of Chemistry, 2011)
The geometries, electronic structures, polarizabilities, and hyperpolarizabilities of organic dye sensitizer 4-(phenylthio)phthalonitrile were studied based on Density Functional Theory (DFT) using the hybrid functional B3LYP. Ultraviolet-Visible (UV-Vis) spectrum was investigated by using a hybrid method which combines CIS-DFT (B3LYP). The absorption bands are assigned to n→π* transitions. The results were showed 4-(phenylthio) phthalonitrile used in Dye Sensitized Solar Cells (DSSC) give a good conversion efficiency.